2021
DOI: 10.1007/s00018-021-03923-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of genomic DNA damage: methods and implications

Abstract: Exposures from the external and internal environments lead to the modification of genomic DNA, which is implicated in the cause of numerous diseases, including cancer, cardiovascular, pulmonary and neurodegenerative diseases, together with ageing. However, the precise mechanism(s) linking the presence of damage, to impact upon cellular function and pathogenesis, is far from clear. Genomic location of specific forms of damage is likely to be highly informative in understanding this process, as the impact of dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 164 publications
0
13
0
Order By: Relevance
“…In this perspective, it is crucial to head the treatments toward medicine based on one’s genetic composition, disease phenotype, and molecular makeup. A useful tool to identify patients who can benefit from specific drugs is genome mapping ( 23 ). Epigenetic alterations are proven to be restored and epigenetic therapies have arisen.…”
Section: From Pharmacogenetics and Pharmacogenomics To Epi-drugs In C...mentioning
confidence: 99%
“…In this perspective, it is crucial to head the treatments toward medicine based on one’s genetic composition, disease phenotype, and molecular makeup. A useful tool to identify patients who can benefit from specific drugs is genome mapping ( 23 ). Epigenetic alterations are proven to be restored and epigenetic therapies have arisen.…”
Section: From Pharmacogenetics and Pharmacogenomics To Epi-drugs In C...mentioning
confidence: 99%
“…Further, click chemistry, Click-Code-Seq, has been successfully applied to label 8-oxo-7,8-dihydroguanine (8-oxo-dG) or 5-hydroxymethylcytosine (5hmdC) sites in DNA prior to next-generation sequencing [54,55]. DNA adduct mapping methods have been reviewed extensively [56][57][58].…”
Section: Amplification-based Mapping Of Dna Adductsmentioning
confidence: 99%
“…Alternatively, the composition of dCPD is reported to contain a higher ratio of cytosine‐containing (T<>C, C<>T) CPD (11) that are more rapidly repaired. Interestingly, this may also correspond to the most frequent mutations seen in nonmelanoma skin cancer (C to T transitions), as repair brings with it an opportunity for mutation (39), and rapid repair may result in decreased fidelity. Finally, an in vitro study in melanocytes suggested that the formation and repair of dCPD may depend on genomic site (40).…”
Section: Findings From In Vivo Modelsmentioning
confidence: 99%